2022
DOI: 10.1088/1361-6463/ac48b0
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple plasmon-induced transparency and tunable multi-frequency switch in monolayer graphene terahertz metamaterial

Abstract: A monolayer graphene metamaterial composed of a graphene block and four graphene strips, which has the metal-like properties in terahertz frequency range, is proposed to generate an outstanding quadruple plasmon-induced transparency (PIT). Additional analyses show that the forming physical mechanism of the PIT with four transparency windows can be explained by strong destructive interference between the bright mode and the dark mode, and the distributions of electric field intensity and electric field vectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Furthermore, by using the control variable method, we studied the effect on the absorption by adjusting the geometric parameters [ 48 ], the opening width a , the cross-width b , the ring width w , and the inner radius r . The corresponding results are suggested in Figure 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by using the control variable method, we studied the effect on the absorption by adjusting the geometric parameters [ 48 ], the opening width a , the cross-width b , the ring width w , and the inner radius r . The corresponding results are suggested in Figure 7 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the pattern size of OPST graphene should not be too large, as this can cause it to couple to adjacent graphene arrays and affect the resonance frequency. Furthermore, by using the control variable method, we studied the effect on the absorption by adjusting the geometric parameters [48], the opening width a, the cross-width b, the ring width w, and the inner radius r. The corresponding results are suggested in Figure 7. Figure 7a,c,e,g displays the changes in absorption efficiencies of each resonance mode, and Figure 7b,d,f,h shows the corresponding shift of the resonant frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research found that m can reach a maximum value of 4.0 m 2 V À1 s À1 at room temperature. 45,46 Thus, it is reasonable to set the graphene carrier mobility m to 4.0 m 2 V À1 s À1 .…”
Section: Structural Model and Theoretical Analysismentioning
confidence: 99%
“…PIT-effect metamaterials are renowned for their extensive potential in various fields, including modulators [36], encoders [37], and sensors [38]. Their unique feature of creating a transparent window significantly slows down photon propagation through the medium, setting a solid groundwork for future advancements in optical communication and storage technologies.…”
Section: Introductionmentioning
confidence: 99%